Promising biomedical applications using superparamagnetic nanoparticles - Yosri A. Fahim; Ibrahim W. Hasani; Waleed Mahmoud Ragab (European Journal of Medical Research)
Abstract Magnetic nanoparticles (MNPs) have emerged as powerful tools in biomedicine due to their distinct physicochemical characteristics, including a high surface-area-to-volume ratio, adjustable size, magnetic sensitivity, and compatibility with biological systems. These properties enable precise control through external magnetic fields, making MNPs highly effective in targeted therapeutic and diagnostic applications. Although not inherently intelligent, they can exhibit programmable and responsive behavior under external influence, enhancing their utility in drug delivery and hyperthermia-based treatments. In the medical field, MNPs have been extensively explored for their role in magnetic resonance imaging (MRI) enhancement, selective drug transport, hyperthermia cancer therapy, and biomolecular separation. Within oncology, they facilitate the direct delivery of therapeutic compounds to tumors, reducing systemic side effects and increasing treatment specificity. Additionally, their capacity to produce localized heat when exposed to alternating magnetic fields makes them instrumental in hyperthermia therapy, where malignant cells are selectively eradicated. A key advantage of MNPs is their adaptable surface chemistry, which allows for functionalization with biocompatible polymers, ligands, and other stabilizing agents. These modifications enhance their stability, minimize immune responses, and optimize their performance in physiological environments. Functionalized MNPs have contributed significantly to improving MRI contrast, refining drug delivery mechanisms, and increasing the effectiveness of hyperthermia treatments. This review examines recent breakthroughs in MNP-based medical technologies, with an emphasis on tumor targeting, drug delivery across the blood–brain barrier, and hyperthermia applications.